Association Between Psoriasis and Dementia: Current Evidence - Liu, Liu; Chen, Si-ting; Li, Hong-jin; Qiang, Yan; Sun, Xiao-ying; Zhou, Ya-qiong; Xing, Meng; Luo, Ying; Ru, Yi; Ding, Xiao-jie; Kuai, Le; Li, Bin; et al. (Frontiers in Aging Neuroscience, 2020)
Background: Psoriasis and dementia are both inflammatory diseases. The association between psoriasis and dementia has rarely been investigated, and the existing results are conflicting. Thus, we conducted this study to evaluate whether an association exists between psoriasis and dementia. Methods: We searched for studies from six databases from inception to July 30, 2020, using subject and free words. RevMan 5.4 was used to calculate the risk ratio (RR) of dementia in the subjects with psoriasis. When heterogeneity was present, a random-effects model was used. Subgroup, sensitivity, and meta-regression analyses were performed using Stata 15.1. Results: Nine studies were identified and included in the study, of which seven that involved a total of 3,638,487 participants were included in the meta-analysis. We found that among the patients with psoriasis (RR: 1.14, 95% confidence interval [CI]: 1.06–1.24, p = 0.0009) and psoriatic arthritis (RR: 2.20, 95% CI: 1.29–3.78, p = 0.004), the proportions of those with nonvascular dementia (RR: 1.13, 95% CI: 1.11–1.15, p <0.00001) and vascular dementia (RR: 1.41, 95% CI: 1.09–1.82, p = 0.009) were higher than that among the patients without psoriasis. Those with dementia were also more likely to develop psoriasis, and those with severe psoriasis were less likely to die from dementia (RR: 1.88, 95% CI: 0.72–4.90, p = 0.020). The meta-regression analysis did not show any significant sources of heterogeneity. Conclusions: The patients with psoriasis and psoriatic arthritis show high prevalence of different types of dementia. Based on the findings of this study, dementia may not be considered a high-risk factor of death from severe psoriasis. However, identification of this potential risk allows early intervention, thereby reducing comorbidities and deaths.